Motion Sickness Mitigation in Autonomous Vehicle: A Mini-Review - Saruchi, S.A.; Ariff, M.H.M.; Zamzuri, H.; Rahman, M.A.A.; Wahid, N.; Hassan, N.; Izni, N.A.; Yakub, F.; Husain, N.A.; Abu Kassim, K.A. (Journal of the Society of Automotive Engineers Malaysia, 2021)
An autonomous vehicle is a rapidly evolving technology that received attention from researchers due to its potential benefits. Besides the advantages, there are also non-negligible issues that need to be overcome in the middle of the autonomous vehicle development process. Among all the challenges, one of the important topics that have not gained adequate consideration is motion sickness (MS). This paper reviews the benefit and challenges of autonomous vehicles, MS factors, the quantifying methods of MS, and the mitigation strategies of MS. Considering the importance of minimizing MS, it is concluded that the number of strategies to lessen MS’s severity is still lacking; hence, requiring more attention from automotive researchers.